(untitled) (Kerala Journal of Psychiatry, 2020)
Pseudocyesis is common, whereas delusion of pregnancy is a rare psychopathology. The shared delusion of pregnancy is even rarer. We present a case from a tribal community where a wife shares her husband’s delusion. It highlights the role of biopsychosocial determinants in forming psychopathology. It also reflects the need for strengthening community psychiatry approach.